2015
DOI: 10.17261/pressacademia.2015312981
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs happiness, personal initiatives and firm performance: evidence from China

Abstract: This article constructed a theoretical model including entrepreneurs' happiness, personal initiative and firm performance, and tested the hypotheses using questionnaire survey and SEM analysis. The path analysis of 660 samples indicates that entrepreneurs' Eudaimonic Well-Being helps to enhance firm performance, but the Hedonic Well-Being has no significant direct effect on firm performance. Eudaimonic Well-Being can promote entrepreneurs to exhibit more task-oriented and relationship-oriented personal initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For example, Guiso et al (2009) showed that trust between inhabitants of different countries is partly explained by the commonality in languages. Personal initiatives of entrepreneurs are greatly related to firm's policy, and thus, influence the performance and value of firms (Song et al, 2015). The cultural heterogeneity data was drawn from the China 9 Economics is currently experiencing a rapid increase in research related to country culture and its impact on behavior and decision-making by individuals, as well as corporations.…”
Section: Controlling For Regional and Cultural Economic Heterogeneitymentioning
confidence: 99%
“…For example, Guiso et al (2009) showed that trust between inhabitants of different countries is partly explained by the commonality in languages. Personal initiatives of entrepreneurs are greatly related to firm's policy, and thus, influence the performance and value of firms (Song et al, 2015). The cultural heterogeneity data was drawn from the China 9 Economics is currently experiencing a rapid increase in research related to country culture and its impact on behavior and decision-making by individuals, as well as corporations.…”
Section: Controlling For Regional and Cultural Economic Heterogeneitymentioning
confidence: 99%
“…For example, Guiso et al (2009) showed that trust between inhabitants of different countries is partly explained by the commonality in languages. Personal initiatives of entrepreneurs are greatly related to firm's policy, and thus, influence the performance and value of firms (Song et al, 2015). The cultural heterogeneity data was drawn from the China 9 Economics is currently experiencing a rapid increase in research related to country culture and its impact on behavior and decision-making by individuals, as well as corporations.…”
Section: Controlling For Regional and Cultural Economic Heterogeneitymentioning
confidence: 99%